Profiles of cognitive impairment in chronic heart failure—A cluster analytic approach - Göpfert, Dennis; Traub, Jan; Sell, Roxane; Homola, György A.; Vogt, Marius; Pham, Mirko; Frantz, Stefan; Störk, Stefan; Stoll, Guido; Frey, Anna (Frontiers in Human Neuroscience, 2023)
Background Cognitive impairment is a major comorbidity in patients with chronic heart failure (HF) with a wide range of phenotypes. In this study, we aimed to identify and compare different clusters of cognitive deficits. Methods The prospective cohort study “Cognition.Matters-HF” recruited 147 chronic HF patients (aged 64.5 ± 10.8 years; 16.2% female) of any etiology. All patients underwent extensive neuropsychological testing. We performed a hierarchical cluster analysis of the cognitive domains, such as intensity of attention, visual/verbal memory, and executive function. Generated clusters were compared exploratively with respect to the results of cardiological, neurological, and neuroradiological examinations without correction for multiple testing. Results Dendrogram and the scree plot suggested three distinct cognitive profiles: In the first cluster, 42 patients (28.6%) performed without any deficits in all domains. Exclusively, the intensity of attention deficits was seen in the second cluster, including 55 patients (37.4%). A third cluster with 50 patients (34.0%) was characterized by deficits in all cognitive domains. Age (p = 0.163) and typical clinical markers of chronic HF, such as ejection fraction (p = 0.222), 6-min walking test distance (p = 0.138), NT-proBNP (p = 0.364), and New York Heart Association class (p = 0.868) did not differ between clusters. However, we observed that women (p = 0.012) and patients with previous cardiac valve surgery (p = 0.005) prevailed in the “global deficits” cluster and the “no deficits” group had a lower prevalence of underlying arterial hypertension (p = 0.029). Total brain volume (p = 0.017) was smaller in the global deficit cluster, and serum levels of glial fibrillary acidic protein were increased (p = 0.048). Conclusion Apart from cognitively healthy and globally impaired HF patients, we identified a group with deficits only in the intensity of attention. Women and patients with previous cardiac valve surgery are at risk for global cognitive impairment when suffering HF and could benefit from special multimodal treatment addressing the psychosocial condition.